Analisis Kesediaan, Komparasi Pendapatan dan Faktor-Faktor yang mempengaruhi Petani Pengguna Combine Harvester dan Konvensional di Desa Sudipayung, Kecamatan Ngampel, Kabupaten Kendal - lufita nur riza irma; Roessali, Wiludjeng; Nurfadillah, Suryani (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2024)
Combine harvester machine is a harvesting machine that can thresh, separate, clean and sort grain at once with low yield loss. The government supports agricultural activities, which is by distributing combine harvester machines through the village government. This study aims to determine the willingness of farmers to adopt a combine harvester machine, differences in the income of conventional farmers and users of a combine harvester machine, and to determined the factors that influence the willingness of farmers to adopt a combine harvester machine. The research method is a survey with descriptive statistics, binary logistic regression and the Marn-Whitney Test. The willingness of farmers to adopt a combine harvester was analyzed descriptively. Differences in income between farmers were analyzed using the Mann-Whitney test. Factors that influence farmers' willingness to adopt were analyzed using binary logistic regression. The results showed that the willingness of farmers to adopt a combine harvester machine was in the moderate category, meaning that there were farmers' hesitation to use the machine repeatedly. There are significant difference income between conventional farmers and users of combine harvester machines. The income of conventional farmers during one growing season is Rp.7,293.516,-/ha and farmers using combine harvester machines are Rp.9,865,203,-/ha. Differences in income are significantly influenced by differences in production costs incurred by farmers during one growing season. Factors that influence farmers' willingness to adopt combine harvester machines include farming experience, farmer's recent education and farmer's level of participation. Farmers' age, land area, and land ownership have no effect on farmers' willingness to adopt combine harvester machines.